Tax potential of municipalities as the basis of regional budgets - N. Z. Zotikov (Вестник университета)
In  the Russian Federation (hereinafter referred to  as RF, Russia), which is  a  federal state with a  three-level budget system, it  is assumed that there is   tax potential at   all levels: federal, regional, and local. With the help of  taxes, the financial basis of   local governments is  formed and the socio-economic development of   municipalities is  ensured. In   developed countries, municipal budgets are formed mainly from the taxes assigned to   them. In   Russia, they continue to  remain the most problematic link in  the country’s budget system. The purpose of   the article is   to study the influence of  the taxes assigned to   local budgets on   the formation of   the tax potential of   the municipalities. Objectives are the following: analysis and assessment of   revenues of   the Russian local budgets in  dynamics, justification of  directions for increasing the tax potential. The methodological basis of   the research is   founded on a  systematic approach, within which the following methods have been used: analysis and synthesis, generalisation, grouping, tabular method, etc. The research has found that over the past years, with the introduction of  the Tax Code of   the RF, problems of   insufficient tax and non-tax revenues remain for most municipalities, low level of   the tax potential and predominance of   interbudgetary transfers in  their budgets are current. Due to  the increasing centralisation of   the tax revenues, the degree of   dependence of   the municipalities on   the federal centre is  high. Without actually enhancing the tax potential of   the municipalities, the development of   the regional economy is   impossible. The re -search results can be   used in   practice when developing economic policy for municipal development.